2007
DOI: 10.1073/pnas.0708559104
|View full text |Cite
|
Sign up to set email alerts
|

Variation in HIV-1 set-point viral load: Epidemiological analysis and an evolutionary hypothesis

Abstract: The natural course of HIV-1 infection is characterized by a high degree of heterogeneity in viral load, not just within patients over time, but also between patients, especially during the asymptomatic stage of infection. Asymptomatic, or set-point, viral load has been shown to correlate with both decreased time to AIDS and increased infectiousness. The aim of this study is to characterize the epidemiological impact of heterogeneity in set-point viral load. By analyzing two cohorts of untreated patients, we qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
556
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 381 publications
(587 citation statements)
references
References 30 publications
19
556
2
Order By: Relevance
“…The number of lineages with A or B labels that merge in the source population is therefore a random variable determined by the sample size, sampling time, and within-host dynamics. In general, this quantity will be smaller than the HIV-1 within-host population size (35)(36)(37), or effective population size (38)(39)(40), and consequently sampling plays an important role in the ability of genetic data to resolve an epidemiologic linkage. Furthermore, first principles predict that as the time between transmission and sampling increases, eventually old lineages will be lost in the derived populations, leading to loss of the paraphyletic signal (Fig.…”
Section: Paraphyletic Signal Predicts Direction Of Transmission But Dmentioning
confidence: 99%
“…The number of lineages with A or B labels that merge in the source population is therefore a random variable determined by the sample size, sampling time, and within-host dynamics. In general, this quantity will be smaller than the HIV-1 within-host population size (35)(36)(37), or effective population size (38)(39)(40), and consequently sampling plays an important role in the ability of genetic data to resolve an epidemiologic linkage. Furthermore, first principles predict that as the time between transmission and sampling increases, eventually old lineages will be lost in the derived populations, leading to loss of the paraphyletic signal (Fig.…”
Section: Paraphyletic Signal Predicts Direction Of Transmission But Dmentioning
confidence: 99%
“…Possibly, one of the best studied pathogens in this regard is HIV. Data for HIV correlating the viral load in serum with probability of infection in a partner suggest a sigmoid relationship (figure 2; [42][43][44]). However, higher viral load also leads to more rapid progression to the terminal AIDS stage [43,45], therefore reducing the time during which transmission can occur (figure 2).…”
Section: Host Infectiousnessmentioning
confidence: 99%
“…However, earlier models have shown that further assumptions would then be needed because if both virulence and transmission rates are linear functions of parasite load, natural selection will always favour the strains with the highest possible level of virulence [51]. One possibility could be to focus on a biological system where these relationships have been parametrized, such as HIV in humans [52], myxomatosis in rabbits [53], Ophryocystis elektroscirrha in monarch butterflies [54] or the cauliflower mosaic virus in turnips [55].…”
Section: Discussionmentioning
confidence: 99%